Multi‐electron Reduction Capacity and Multiple Binding Pockets in Metal–Organic Redox Assembly at Surfaces. Issue 21 (18th March 2019) - Morris, Tobias W.; Huerfano, I. J.; Wang, Miao; Wisman, David L.; Cabelof, Alyssa C.; Din, Naseem U.; Tempas, Christopher D.; Le, Duy; Polezhaev, Alexander V.; Rahman, Talat S.; Caulton, Kenneth G.; Tait, Steven L.
Abstract: Metal–ligand complexation at surfaces utilizing redox‐active ligands has been demonstrated to produce uniform single‐site metals centers in regular coordination networks. Two key design considerations are the electron storage capacity of the ligand and the metal‐coordinating pockets on the ligand. In an effort to move toward greater complexity in the systems, particularly dinuclear metal centers, we designed and synthesized tetraethyltetra‐aza‐anthraquinone, TAAQ, which has superior electron storage capabilities and four ligating pockets in a diverging geometry. Cyclic voltammetry studies of the free ligand demonstrate its ability to undergo up to a four‐electron reduction. Solution‐based studies with an analogous ligand, diethyldi‐aza‐anthraquinone, demonstrate these redox capabilities in a molecular environment. Surface studies conducted on the Au(111) surface demonstrate TAAQ′s ability to complex with Fe. This complexation can be observed at different stoichiometric ratios of Fe:TAAQ as Fe 2p core level shifts in X‐ray photoelectron spectroscopy. Scanning tunneling microscopy experiments confirmed the formation of metal–organic coordination structures. The striking feature of these structures is their irregularity, which indicates the presence of multiple local binding motifs. Density functional theory calculations confirm several energetically accessible Fe:TAAQ isomers, which accounts for the non‐uniformity of the chains. Abstract : Reduction capacity and binding pockets : A new redox‐active tetra‐aza‐anthraquinone ligand undergoes on‐surface redox complexation with Fe and assembly into 1D chains on the Au(111) surface. The number of binding pockets of the new ligand outpaces the reduction capacity, allowing for multiple M−L binding geometry options, which manifests as a stable, but meandering metal–organic chain structure.